The Relationship Between Emotional Intelligence and Cyberbullying Behavior in Adolescents in Salatiga: Hubungan Antara Kecerdasan Emosional Dengan Perilaku Cyberbullying Pada Remaja di Salatiga - Sting, Nataliinn (Psikologia : Jurnal Psikologi, 2019)
This study is conducted to examine the correlation between emotional intelligence and cyberbullying behaviour among teenagers in Salatiga. It involved 405 teenagers aged 15-17 years old (247 girls and 158 boys). Data were taken using The Assessing Emotion Scale of Schutte, Malouff, dan Bhullar (2009), consisted of 33 items with validity coefficient 0,843, to examine validity coefficient, and The Cyber-Bullying Questionnaire of Esther Calvete, Izaskun Orue, Ana Estévez, Lourdes Villardón, and Patricia Padilla (2010), consisted of 16 items with validity 0,839, to examine the variable of the behaviour. It was analyzed using Spearman's rank correlation coefficient in SPSS 16.0 for windows. The results showed a significant negative correlation between emotional intelligence and cyberbullying behaviour with rxy = -0,126 dan p = 0,006 (p < 0,05).